Determination of Some Heavy Metals in Eye Shadows Cosmetics - Moniem Ahmed, Hatem Abdel; Ahmed Al-Qahtani, Khairia Mohamed; Emara, Hanan; Janjua, Muhammad Naeem; Alhafez, Nada; Al-Otaibi, Mashaeel Bijad (Asian Journal of Chemistry, 2017)
Minor quantities of several heavy metals have been documented in cosmetic products as impurities which may lead to various types of skin allergies through percutaneous absorption. This study determined the concentration of heavy metals present in the various samples of eye shadows available in Riyadh markets of Saudi Arabia. A total of 21 popular international eye shadow brands from China, France, Italy and Ireland were tested for the presence of some toxic heavy metals. Eye shadows were categorized in three different types (cheap, medium and expensive) on the base of their price. Eye shadow samples were acid digested in a microwave and contents of lead, cadmium and arsenic were measured by graphite furnace atomic absorption spectroscopy (GFAAS), while mercury was quantified by flame atomic absorption spectrometry (FAAS). Results showed that the mean concentration of mercury, arsenic and cadmium were more or less similar in all the three categories (cheap, medium and expensive) of eye shadow samples, whereas the concentration of cadmium was fairly high in cheap eye shadow samples as compared to medium and expensive priced quality. Lead concentration was higher in expensive eye shadows samples than medium and cheap priced samples. This study showed that the mean concentration of toxic heavy metals in all the eye shadow samples were below the US FDA and SFDA permissible limits for cosmetic products with the exception that mercury content in eye shadows samples was higher than SFDA.